SUN-607 Iron Parameters in Patients with Partial Lipodystrophy and Impact of Metreleptin Therapy - Boutros, Sabine (J Endocr Soc, 2020)
Introduction Intriguing rodent studies and epidemiological data suggest that iron metabolism and adipocytokines crosstalk to regulate glucose metabolism and fuel storage. Iron parameters have not been previously studied in patients with lipodystrophy whereas increased iron stores have been associated with type 2 diabetes. In this study, we sought to investigate the status of iron parameters in patients with partial lipodystrophy (PL) and to interrogate whether the adipocyte hormone leptin can modulate iron metabolism. Methods Serum samples of 19 patients with PL (age: 42, IQR: 34-57, M/F: 3/16) were used from an open-label study previously performed at the University of Michigan evaluating the efficacy of metreleptin in nonalcoholic steatohepatitis (NCT01679197) to measure ferritin, hepcidin, iron, and transferrin soluble receptor levels. High-sensitivity C-reactive protein (hs-CRP) levels were also determined as broader changes in inflammatory pathways may potentially impact circulating ferritin levels. Results were integrated into an existing database of metabolic parameters. Data are presented as median, IQR. Results At baseline, ferritin levels were positively correlated with fasting glucose (r = 0.533; p = 0.023) and HbA1c (r = 0.510; p = 0.031). During the 6 months of therapy period, HbA1c (9.2%, 7.3-10.3 vs. month-3: 8.6%, 7.7-9.6; p = 0.099; and month-6: 8.5%, 6.8-9.5; p = 0.264), triglyceride levels (346 mg/dL, 240-1771 vs. month-3: 346 mg/dl, 237-479; p = 0.047; and month-6: 295 mg/dl, 207-495; p = 0.091), and hepatic fat (12.7%, 9.8-20.6 vs. month-6: 8.9%, 7.0-11.0; p = 0.031)} decreased. Reductions were observed in serum ferritin after metreleptin treatment (83.23 ng/mL, 76.43-178.97 vs. month-3: 73.79 ng/ml, 68.30-78.59; p = 0.007; and month-6: 61.03 ng/mL, 46.45-157.74; p = 0.004). There was a tendency for hepcidin and iron to be decreased, but this did not reach statistical significance. On the other hand, there were notable reductions in hs-CRP levels at 6 months compared to baseline (2.94 mg/L, 1.30-4.80 vs. 1.6 mg/L, 1.00-6.30; p = 0.012). Baseline leptin level was inversely correlated with percent reduction in hs-CRP at month-6 (r = -0.685; p = 0.001). Also, modest correlations were observed between changes in serum iron and triglycerides (r = 0.491, p = 0.033) and hepatic fat (r = 0.412, p = 0.079). Conclusions We observed a significant relationship between ferritin and glucose control in a group of patients with PL. Metreleptin therapy was associated with improvements in triglycerides and hepatic fat and there were also significant decreases in ferritin and hs-CRP levels. These results raise the possibility that metreleptin therapy influences iron metabolism. However, whether the decrease in ferritin indicates a decrease in iron stores or is mediated by an effect on inflammation remains unknown.